Models of Antenatal Care: a pilot study to explore a new quality care framework - Symon, Andrew (University of Dundee, 2018)
Systematic reviews (e.g. Sandall et al. 2015) have demonstrated a link between midwifery-led continuity of care models and improved Clinical, Psychosocial and Organisational (CPO) outcomes, including preterm birth and breastfeeding rates. However, the underlying causal mechanisms within these models are not understood, and trial reports rarely detail all the relevant contextual factors for the intervention and control groups. This pilot study will test the use of focus groups with service users and providers across NHS Tayside and NHS Fife in an exploration of their perceptions of the antenatal care model with which they are familiar. The focus groups will use as their starting point the Quality Maternal and Newborn Care (QMNC) Framework published in The Lancet Series on Midwifery. While this Framework for quality care is well-evidenced and peer reviewed, it has yet to be determined how service users and providers in different care models understand or experience the components and characteristics of care which the Framework describes. These pilot focus groups are therefore needed to explore how service users and service providers perceive or understand how the characteristics of care specified in the Framework apply to the model of care with which they are most familiar. Analysing these interviews will help us to understand better how to design largerscale fieldwork that will result in development of a care model evaluation toolkit. This will allow us, other researchers, the NHS and policy-makers to assess service provision across a range of settings, models of care and regions. This pilot study will be conducted in three varying care model settings within Tayside and Fife: in-hospital continuity midwifery; out-of-hospital continuity midwifery; ‘standard’ care with no or little prescribed continuity element (which in practice often means in-hospital obstetric-led), and will be guided by Patient and Public Involvement. We emphasise that while settings and care models overlap, they are not synonymous. ‘Continuity’ is not restricted to midwifery care; and ‘standard’ care varies according to local circumstances.